Nanobody mediated crystallization of an archeal mechanosensitive channel - Moberg, Per (2014)
Mechanosensitive channels (MS) are integral membrane proteins and allow bacteria to survive sudden changes in external osmolarity due to transient opening of their pores. The efflux of cytoplasmic osmolytes reduces the membrane tension and prevents membrane rupture. Therefore these channels serve as emergency valves when experiencing significant environmental stress. The preparation of high quality crystals of integral membrane proteins is a major bottleneck for structure determination by X-ray crystallography. Crystallization chaperones based on various protein scaffolds have emerged as promising tool to increase the crystallization probability of a selected target protein. So far archeal mechanosensitive channels of small conductance have resisted crystallization in our hands. To structurally analyse these channels, we selected nanobodies against an archeal MS channel after immunization of a llama with recombinant expressed, detergent solubilized and purified protein. Here we present the characterization of 23 different binders regarding their interaction with the channel protein using analytical gel filtration, western blotting and surface plasmon resonance. Selected nanobodies bound the target with affinities in the pico- to nanomolar range and some binders had a profound effect on the crystallization of the MS channel. Together with previous data we show that nanobodies are a versatile and valuable tool in structural biology by widening the crystallization space for highly challenging proteins, protein complexes and integral membrane proteins.